A production systems study on Philippine Electric Company - Alban, Margie C. (College of Engineering, 1996)
The Philippine Electric Company (PHILEC) is considered as the leading company in the country today. They are the major supplier of Distribution and Power Transformers to a number of companies. But 80% of the company?s demand comes from Meralco. January of this year, Meralco shifted from the Conventional to Low Loss design. Low loss transformers are bigger, heavier, wider and more efficient, thus they have longer cycle times. As compared to other years, Meralco?s demand for this year increased. Hence, the company has to look into their existing capacity to check whether these capacities can still meet the increasing demand. A documentation of the company?s existing system was done using the worker?s Daily production Report and with added information from interviews with the Production Planning and Control, Accounting, Engineering, foremen and workers as well. Analysis of the existing system showed that the company indeed has problems regarding their man and machine hours. Using the tools in capacity planning, the group therefore recommended machines and labor be added to certain operations in the Coil, Core and Assembly sections. In relation to the proposed solutions, corresponding changes in the company?s current layout was also done.